Associations between depressive symptom clusters and care utilization and costs among community‐dwelling older adults. (14th October 2021) - Lu, Shiyu; Zhang, Yan; Liu, Tianyin; Leung, Dara K. Y.; Kwok, Wai‐Wai; Luo, Hao; Tang, Jennifer; Wong, Gloria H. Y.; Lum, Terry Y. S.
Abstract: Objectives: Whether and how symptom clusters are associated with care utilization remains understudied. This study aims to investigate the economic impact of symptom clusters. Methods: We conducted cross‐sectional analyses of data collected from 3255 older adults aged 60 years and over in Hong Kong using the Patient Health Questionnaire‐9 and the Client Service Receipt Inventory to measure depressive symptoms and service utilization to calculate 1‐year care expenditure. Based on Research Domain Criteria framework, we categorized depressive symptoms into four clusters: Negative Valance Systems and Externalizing (NVSE; anhedonia and depression), Negative Valance Systems and Internalizing (guilt and self‐harm), Arousal and Regulatory Systems (sleep, fatigue, and appetite), and Cognitive and Sensorimotor Systems (CSS; concentration and psychomotor). Two‐part models were used with four symptom clusters to estimate economic impacts on care utilization. Results: Core affective symptoms had the largest economic impact on non‐psychiatric care expenditure; a one‐point increase in NVSE was associated with USD 571 additional non‐psychiatric care expenditure. The economic impacts of CSS on non‐psychiatric care expenditure was attenuated when the severity level of NVSE was higher. Conclusions: Our findings highlight the importance of understanding economic impacts on care utilization based on symptom profiles with a particular emphasis on symptom combinations. Policymakers should optimize care allocation based on older adults' depressive symptom profiles rather than simply considering their depression sum‐score or the severity defined by cut‐off points. Key points: Whether and how symptom clusters are associated with care utilization remains understudied We found that the economic impact of four depressive symptom clusters and their interactions were heterogeneous across the health, social, and rehabilitation care sectors Core affective symptoms had the largest economic impact on non‐psychiatric care expenditure Policymakers should optimize care allocation, taking account of older adults' depressive symptom profiles